Planetes. volume 1 - Yukimura, Makoto, 1976- (Dark Horse Manga, 2015)
It's the 2070s, and mankind has conquered space, making interplanetary travel possible and igniting the imaginations of the world. It's also vastly increased the amount of dangerous space debris, and someone has to clean it up. Hachimaki, Yuri, and Fee are a crew on that beat.